Congenital Myasthenia and Facial Malformations - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1990)
A new genetic syndrome of congenital myasthenia with distinctive ethnic clustering and associated facial malformations transmitted as an autosomal recessive disorder is reported from the Departments of Neurology and Medical Genetics, Chaim Sheba Medical Center, Tel Hashcmer, Sackler School of Medicine, Tel Aviv University, Israel.